2020
DOI: 10.1002/cnr2.1225
|View full text |Cite
|
Sign up to set email alerts
|

The results of the intensive phase of complete decongestive therapy and the determination of predictive factors for response to treatment in patients with breast cancer related‐lymphedema

Abstract: Background: Lymphedema is a common complication of breast cancer or its treatment. The gold standard treatment for lymphedema is complete decongestive therapy. There are few studies about the predictive factors for the effectiveness of complete decongestive therapy.Aim: To evaluate the results of the intensive phase of complete decongestive therapy, and to determine the predictive factors for the response to treatment in patients with breast cancer-related lymphedema.Methods and Results: Fifty-seven patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Intensive phase of CDT was proved to have a positive influence on lymphedema reduction with effects seen despite previous treatment strategy [45,46]. Keskin et al showed that the benefits were greater if the CDT was applied in the early lymphedema stage (stage I) [45]. Findings were confirmed by Borman et al, who reported that improvements in volume were related negatively with the stage of BCRL, and additionally, with the duration of the disease [47].…”
Section: Complete Decongestive Therapy (Cdt)mentioning
confidence: 93%
See 1 more Smart Citation
“…Intensive phase of CDT was proved to have a positive influence on lymphedema reduction with effects seen despite previous treatment strategy [45,46]. Keskin et al showed that the benefits were greater if the CDT was applied in the early lymphedema stage (stage I) [45]. Findings were confirmed by Borman et al, who reported that improvements in volume were related negatively with the stage of BCRL, and additionally, with the duration of the disease [47].…”
Section: Complete Decongestive Therapy (Cdt)mentioning
confidence: 93%
“…It consists of a life-long self-care therapy including compression therapy, exercises, and selfmade MLD provided with various frequency [44]. Intensive phase of CDT was proved to have a positive influence on lymphedema reduction with effects seen despite previous treatment strategy [45,46]. Keskin et al showed that the benefits were greater if the CDT was applied in the early lymphedema stage (stage I) [45].…”
Section: Complete Decongestive Therapy (Cdt)mentioning
confidence: 99%
“…Сочетанное использование методов терапии на протяжении всей жизни пациентов с ПМОК может демонстрировать удовлетворительные результаты [26,[43][44][45][46][47][48][49][50][51][52][53][54]. В первую очередь назначают комплексную противоотечную терапию (complex decongestive therapy -CDТ).…”
Section: диагностика постмастэктомического синдрома клиническая диагн...unclassified
“…В первую очередь назначают комплексную противоотечную терапию (complex decongestive therapy -CDТ). Она включает в себя мануальный лимфатический дренаж, пневмокомпрессионное лечение, индивидуальные физические упражнения и уход за кожей [43][44][45][46][47][48][49]. Применяют компрессионный эластический трикотаж, обеспечивающий статическую компрессию (минимум 30 мм рт.…”
Section: диагностика постмастэктомического синдрома клиническая диагн...unclassified
“…Conservative treatments for BCRL include manual lymphatic drainage (MLD), compression bandaging and garments, exercise, and skin care, which are often provided collectively as complete decongestive therapy (CDT). CDT is considered the mainstay of BCRL conservative treatment and is conducted in a decongestive phase, which is provided by a certified lymphedema practitioner, and a maintenance phase, which is conducted as self-care by the patient [ 12 •]. Sequential pneumatic compression and elastic taping are additional modalities that compliment CDT in the management of BCRL [ 13 ].…”
Section: Introductionmentioning
confidence: 99%